2020
DOI: 10.1155/2020/8406846
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Intestinal Microbiota in 3-Deoxyglucosone-Induced Prediabetic Rats

Abstract: Our previous research suggests that 3-deoxyglucosone (3DG), formed in the caramelization course and Maillard reactions in food, is an independent factor for the development of prediabetes. Since the relationship between type 2 diabetes (T2D) and intestinal microbiota is moving from correlation to causality, we investigated the alterations in the composition and function of the intestinal microbiota in 3DG-induced prediabetic rats. Rats were given 50 mg/kg 3DG by intragastric administration for two weeks. Micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 37 publications
0
22
1
Order By: Relevance
“…As shown in Figure 7B , after dietary intervention with MBPs, changes in gene expression affected several pathways, specifically, the pyruvate fermentation to acetone pathway, succinate fermentation to butanoate pathway, acetyl-CoA fermentation to butanoate II pathway, adenosine nucleotide degradation II pathway, guanosine nucleotide degradation III pathway, purine nucleotide degradation I (anaerobic) pathway, and purine nucleotide degradation II (aerobic) pathway. Cai et al found that the metabolic function of HFD-induced diabetic mice was inhibited and the function of amino acid metabolism was decreased ( 34 ). This finding is consistent with the results of the present study.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 7B , after dietary intervention with MBPs, changes in gene expression affected several pathways, specifically, the pyruvate fermentation to acetone pathway, succinate fermentation to butanoate pathway, acetyl-CoA fermentation to butanoate II pathway, adenosine nucleotide degradation II pathway, guanosine nucleotide degradation III pathway, purine nucleotide degradation I (anaerobic) pathway, and purine nucleotide degradation II (aerobic) pathway. Cai et al found that the metabolic function of HFD-induced diabetic mice was inhibited and the function of amino acid metabolism was decreased ( 34 ). This finding is consistent with the results of the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Of the differentially abundant microbes, Candidatus Soleaferrea stands out for being absent in fCD infants but present in approximately 20% of the control cohorts. There is evidence that Candidatus Soleaferrea , which was absent in fCD infants, has anti-inflammatory properties, but this genus has also been correlated with several autoimmune diseases including CD ( Cai et al., 2020 ; Cao et al., 2021 ; Zou et al., 2022 ). Within each genus, species are diverse and have a range of metabolic features, which can have various consequences on host physiology.…”
Section: Discussionmentioning
confidence: 99%
“…Within the limitations of their study, the authors claimed that the gut microbiota may mediate the influence of periodontitis on prediabetes (57). On the other hand, studies found that Candidatus Soleaferrea tends to have a higher abundance in controls as compared to a rat prediabetic condition (58). Interestingly, the study found that colon Glucagon-like peptide-2 (GLP-2) was positively correlated with an abundance of Candidatus Soleaferrea (58).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, studies found that Candidatus Soleaferrea tends to have a higher abundance in controls as compared to a rat prediabetic condition (58). Interestingly, the study found that colon Glucagon-like peptide-2 (GLP-2) was positively correlated with an abundance of Candidatus Soleaferrea (58). GLP-2, secreted from the metabolites (e.g., SCFA) of gut microbiota, is typically considered a trophic hormone involved in maintaining intestinal epithelial morphology and function.…”
Section: Discussionmentioning
confidence: 99%